Computer-Assisted Instruction in Support of Beginning Reading Instruction: A Review - Blok, H.; Oostdam, R.; Otter, M. E.; Overmaat, M. (Review of educational research, 2002)
How effective are computer-assisted instruction (CAI) programs in support- ing beginning readers? This article reviews 42 studies published from 1990 onward, comprising a total of 75 experimental comparisons. The corrected overall effect size estimate was d = 0.19 (± 0.06). Effect sizes were found to depend on two study characteristics: the effect size at the time of pre-testing and the language of instruction (English or other). These two variables accounted for 61 percent of the variability in effect sizes. Although an effect size of d = 0.2 shows little promise, caution is needed because of the poor quality of many studies.